Antibacterial Activity Test of Scleria sumatrensis Leaf Extract against Staphylococcus aureus in Vitro - Douglas N. Pareta; Reky R. Palandi; Selvana S. Tulandi; Juliani R. Turang; Alter Y. Runtu (FMIPA UKIT, 2025)
Staphylococcus aureus bacteria is one of the important pathogens that can cause various types of infections, ranging from mild ones such as folliculitis and impetigo to life-threatening conditions such as nosocomial pneumonia, osteomyelitis, endocarditis, sepsis, and toxic shock syndrome. Due to its ability to develop resistance to antibiotics, new alternative treatments are needed, one of which is from natural ingredients. In this study, the antibacterial activity of Scleria sumatrensis extract was tested against Staphylococcus aureus with a concentration variation of 100 - 500 µg / disc. The results showed that at a concentration of 100 ?g / disc, the extract provided antibacterial activity in the moderate category, while at a concentration of 200 to 500 ?g / disc, the activity produced was included in the strong category. These findings indicate that Scleria sumatrensis extract has the potential as a natural antibacterial agent against Staphylococcus aureus, so it is worthy of further development as an alternative therapy for infections caused by S. aureus bacteria.